Слава земли Якшурской: очерки, зарисовки разных лет / В. А. Никитин, Г. К. Перевозчиков - Никитин Валериан Арсентьевич (Удмуртия, 2002)
Экземпляры: Ч/з (20160329) / Инвентарный номер: 103902 / Цена: 30.00 / Авт.знак: Н 62 / ГРНТИ: 03 / ББК: 63.3(2Рос.Удм)